Advance in glacier modelling : GIS and oriented programming approach applied on whittier glacier, Alaska - Begnardi, L. (2019)
The global warming affects drastically the glaciers melting, a fact for which the glaciers from Alaska are continuously retreating. Based on Geographical Information System and oriented programming, we have defined a new method to model the glaciers. The Whittier Glacier from South Alaska was analysed in the last 30 years and it was modelled under climate conditions of the 21st century. The glacier modelling has come out from calculations of annual retreat rate, the hemisphere, the latitude, the annual temperature, the precipitation, the altitude data, and the aspect of flow direction. The prediction model of Whittier Glacier shows a value of 1.0544 km² of losing ice area up to year 2030, a value of 2.2184 km² of retreat area up to 2050, a value of 3.9704 km² up to 2080, and a value of 5.1524 km² up to 2100. We estimate a total loss ice volume related to this melting area of 0.3393 km³. The future scenario indicates a glacier volume reduction of 84.89% up to 2050. These findings are useful for glaciologists, but also the paper contributes to Alaskan glaciers knowledge.